2014
DOI: 10.1152/ajprenal.00212.2013
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 5 inhibition ameliorates angiontensin II-induced podocyte dysmotility via the protein kinase G-mediated downregulation of TRPC6 activity

Abstract: The emerging role of the transient receptor potential cation channel isotype 6 (TRPC6) as a central contributor to various pathological processes affecting podocytes has generated interest in the development of therapeutics to modulate its function. Recent insights into the regulation of TRPC6 have revealed PKG as a potent negative modulator of TRPC6 conductance and associated signaling via its phosphorylation at two highly conserved amino acid residues: Thr(69)/Thr(70) (Thr(69) in mice and Thr(70) in humans) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…These effects have been suggested to be primarily mediated by cGMP-mediated protein kinase-G activation, secondary to phosphodiesterase type 5 inhibitor (PDE5i)-induced elevation of the NO-derived cGMP pool. 19,27,28 PF-00489791 was safe and generally well-tolerated when administered at a dose of 20 mg daily for 12 weeks in T2DM subjects with overt DN. The most commonly observed AEs in the present study were consistent with those reported in subjects with mild-to-moderate hypertension treated with PF-00489791 for 28 days, 29 including headaches and upper gastrointestinal events.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These effects have been suggested to be primarily mediated by cGMP-mediated protein kinase-G activation, secondary to phosphodiesterase type 5 inhibitor (PDE5i)-induced elevation of the NO-derived cGMP pool. 19,27,28 PF-00489791 was safe and generally well-tolerated when administered at a dose of 20 mg daily for 12 weeks in T2DM subjects with overt DN. The most commonly observed AEs in the present study were consistent with those reported in subjects with mild-to-moderate hypertension treated with PF-00489791 for 28 days, 29 including headaches and upper gastrointestinal events.…”
Section: Discussionmentioning
confidence: 97%
“…[15][16][17] Specifically, PDE5 inhibition-mediated elevation of cGMP in podocytes attenuates podocyte damage in diabetic rats, resulting in decreased albuminuria, 18 likely through correction of podocyte dysmotility as suggested by in vitro data. 19 The first clinical study to suggest translation of the PDE5-related preclinical findings was conducted by Grover-Páez et al who demonstrated that administration of a PDE5 inhibitor once daily for 30 days to microalbuminuric T2DM patients significantly reduced albuminuria. 20 To further assess the renoprotective effect of chronic PDE5 inhibition in DN, the present study evaluated the safety and efficacy of the novel, selective, and long-acting PDE5 inhibitor, PF-00489791, in subjects with T2DM and overt DN receiving ACEi or ARB background therapy.…”
mentioning
confidence: 99%
“…Reduced channel suppression by PKG1α oxidation fits this observation. Redox sensitivity of PKG1α suppression of TRPC6 may also have therapeutic implications beyond the heart, including in dystrophinopathies (24) and glomerulosclerosis (26,27), where ROS and TRPC6 play a pathophysiological role. Future studies are needed to identify the protein partners that control PKG1α translocation and develop strategies to selectively sustain its reduced state to maximize the efficacy of its activation against myocardial disease.…”
Section: The Journal Of Clinical Investigationmentioning
confidence: 99%
“…Furthermore, Canaud et al (7) described a potential mechanism for sirolimus-induced proteinuria via the mTORC2-dependent inhibition of AKT2 phosphorylation in podocytes. Most recently, Hall et al (22) demonstrated that phosphodiesterase-V inhibitors ameliorated ANG II-induced podocyte dysmotility via the PKG-mediated downregulation of transient receptor potential cation channel 6 (TRPC6) activity. Finally, using a reverse genetics approach, angiopoietin-like 4 (ANGPT4) was identified as a podocyte-secreted inducer of GBM injury and NS, making ANGPT4 a promising novel therapeutic target for minimal-change disease (MCD) (9).…”
Section: Clinical Translation Of Genetic Findings and Barriers To Tramentioning
confidence: 99%
“…However, improvements in our understanding of the mechanisms of TRPC6-mediated podocyte injury in FSGS have not been matched by therapeutic advances. While pharmacological therapies have shown promise in modulating the activity of TRPC6 in vitro (22), these findings have not translated into clinically useful therapeutic tools. Some of the factors responsible for this are 1) the lack of disease-specific cell lines for in vitro modeling and 2) unavailability of suitable animal models for NS.…”
Section: Clinical Translation Of Genetic Findings and Barriers To Tramentioning
confidence: 99%